Normal Magnetic Resonance Imaging Anatomy of the Capsular Ligamentous Supporting Structures of the Knee. Issue 4 (November 2016) - Gimber, Lana H.; Hardy, Jolene C.; Melville, David M.; Scalcione, Luke R.; Rowan, Andrew; Taljanovic, Mihra S.
Recognition of the normal magnetic resonance (MR) imaging appearances of the capsular ligaments of the knee is of great importance. These ligaments contribute to stability of the knee joint and are frequently injured. In this article, we describe the normal MR imaging anatomy of the capsular ligaments of the knee including the lateral and medial collateral ligamentous complexes, the extensor mechanism, and the supporting ligamentous structures of the proximal tibiofibular joint. Normal MR imaging findings and important anatomic variants of the neurovascular structures of the knee are also described.